J.BAZARBAEVTÍŃ DÁSTÚRLER, RUWXÍYLÍQ HÁM ÁDEP – IKRAMLÍLÍQ HAQQÍNDAǴÍ TÁRBIYALÍQ KÓZQARASLARÍ - Joldasbaev, P.M. (SCIENCE and SOCIETY, 2020)
The article presents the ideas and opinions of Academician Jumanazar Bazarbaev about the role of customs, spirituality, ethics and aesthetics in education of the youth and their role in the development of society.